2009
DOI: 10.1021/ef800668u
|View full text |Cite
|
Sign up to set email alerts
|

Thermogravimetric Quantification of Biodiesel Produced via Alkali Catalyzed Transesterification of Soybean oil

Abstract: The aim of this study was to demonstrate the use of thermogravimetric analysis (TGA) as a potential screening method for monitoring biodiesel production by transesterification of soybean oil with methanol. Soybean oil and commercially available biodiesel were mixed in varying proportions by weight as standards. In addition, mixtures of different biodiesel/soybean oil ratios were also created by periodically interrupting base-catalyzed transesterification of soybean oil with methanol. The mixtures produced by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 21 publications
(24 reference statements)
1
42
1
5
Order By: Relevance
“…The purity of the biodiesel was determined from the weight lost due to volatilization of biodiesel in thermogravimetric curves. 17 Kinematic viscosity was measured at 40 °C using an Ubbelohde viscometer following the procedure described in ASTM D-445. The density was determined by measuring the specific gravity with a hygrometer (ROBSAN-1107, México) with a range of 0.80 to 0.90 and a Polyscience 9106A11B circulating bath following the ASTM D-1298 standard.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purity of the biodiesel was determined from the weight lost due to volatilization of biodiesel in thermogravimetric curves. 17 Kinematic viscosity was measured at 40 °C using an Ubbelohde viscometer following the procedure described in ASTM D-445. The density was determined by measuring the specific gravity with a hygrometer (ROBSAN-1107, México) with a range of 0.80 to 0.90 and a Polyscience 9106A11B circulating bath following the ASTM D-1298 standard.…”
Section: Methodsmentioning
confidence: 99%
“…19,20 The ability of TGA to determine the biodiesel purity has been compared with nuclear magnetic resonance (NMR) spectroscopy and the result is an acceptable discrepancy of ±1.5%. 17 A similar principle can be used to determine the percentage of oxidation products present in a biodiesel sample, as described below. Figure 2 shows a typical thermal decomposition curve of a FB sample used in this study.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…However, the waste vegetable oil begins its thermal degradation at approximately 350°C. Accordingly, the percentage of biodiesel conversion at the prepared sample may be calculated using TGA analysis [22]. The thermal gravimetric analysis of the biodiesel produced sample at optimum conditions using KM micro-mixer was compared with its parent waste oil and the biodiesel prepared sample using high inlet reactant flow rate of 200 mL/hr.…”
Section: Characterization Of Produced Biodieselmentioning
confidence: 99%
“…The method can also be adopted to analyse the thermal behavior of biodiesel. Currently, several methods are available in the literature that can be used to calculate the kinetic parameters (Chand et al, 2009). The kinetic analysis used for the thermal conversion of the biodiesel is discussed below:…”
Section: 21non-isothermal Analysismentioning
confidence: 99%
“…Chand et al (2009) studied the effectiveness of TGA and found that TGA is an effective method, which is typically within ±1.5% relative to proton NMR method. Dantas et al (2007) studied the thermal stability and decomposition of biodiesel using TGA -DTA curves obtained using a simultaneous DTA/TG analyzer (SDT 2960, TA Instruments) in air and nitrogen (100 ml/ min flow rate) in the temperature range 30 0 -600°C at a heating rate of 10°C/ min using about 20 mg of sample in alumina crucible.…”
Section: Introductionmentioning
confidence: 99%